"Because They Are Me": Dress and the Making of Gender. Issue 4 (2nd October 2017) - Shefer, Tamara; Ratele, Kopano; Clowes, Lindsay
ABSTRACT: Young people in contemporary South Africa inhabit a multiplicity of diverse, often contradictory, economic and socio-cultural contexts. These contexts offer a range of possibilities and opportunities for the affirmation of certain identities and positionalities alongside the disavowal of others. Dress – clothes, accessories and body styling – is one of the key components through which, within specific social conditions, people perform these identities. In making statements about themselves in terms of these multiple and intersecting group (or social) historical identities, the meanings soaked into people's dress simultaneously speak to the present and their aspirations for the future. This article reports on a study that explored how a group of third year students at a South African university use dress to negotiate the multiple and intersecting identities available to them in a context characterised by neoliberal democracy and market ideologies that continue to be mediated by the racialised legacies of apartheid. The study employed a qualitative feminist discourse analysis to consider 53 semi-structured in-depth interviews conducted by third year students with other students on campus as part of an ongoing project exploring gender productions and performance. The discussion focuses on student understandings of ways in which contemporary clothes and dress signal gender. The research suggests that while there are moments in which clothes are acknowledged as expressions that can reinforce or challenge inequalities structured around gender, participants are also strongly invested in neoliberal consumerist understandings of clothes as accessories to an individualised self in ways that reinforce neoliberal market ideologies and reinstate hegemonic performances of gender.